Revenue optimization strategies in budget hotels: Evidence from independent hotel management in Malang - Mufarrohah Mufarrohah; Didik Rocki Wahyono; A. Faidlal Rahman (School of Tourism, Universitas Ciputra Surabaya, 2026)
Budget hotels are hotels with a lower-middle market segmentation. Having a broader target market, but with the rapid growth of competition caused by the establishment of many budget hotels, it has become quite a significant challenge, especially in terms of management and business sustainability. The management of budget hotels can generally be done independently or by using a Virtual Hotel Operator (VHO), but both have an impact on revenue optimization. Given these issues, the author intends to conduct research on the implementation of profit optimization in budget hotels located in the city of Malang. This study uses a descriptive qualitative approach to systematically illustrate the optimization of hotel revenue. The research results show that the optimization of budget hotel revenue is carried out thru independent management without involving a Virtual Hotel Operator (VHO). In addition, to increase the occupancy of budget hotels, the role of Online Travel Agents (OTAs) is also involved by limiting the share according to the level of visits. In addition, to enhance revenue optimization, it is not always accompanied by cost-cutting. This is evidenced by budget hotels that allocate funds for the use of a Property Management System (PMS) in the form of a Visual Hotel Program (VHP) with a rental system intended for data accuracy and asset security.